State of the Art About COVID-19's Impact on Santiago University, Cape Verde - Sarmento, Eduardo Moraes (2022)
The COVID-19 pandemic become a critical challenge for the higher education sector worldwide. Under such a circumstance, the exploration of the capacity of this sector to adapt to such a state of uncertainty has become more of huge importance. In this chapter, we critically reflect on the Cape Verdean teaching experience during the early COVID-19 lockdown in this country. This is an exploratory case study based on a qualitative approach with an aim to reflect about new practices of teaching under a pandemic emergency. Based on the teaching experience of teaching in Santiago University, we explain how this university has changed from a face-to-face to an online teaching system and stress the challenges and opportunities that appear from this transition process. This chapter concludes that this strategy has become an opportunity to the university since it consistently raised the number of international students cooperating with them and also that the more adaptive and resilient approaches to online teaching were also a success.